DETERMINAN MINAT MAHASISWA AKUNTANSI MENJADI KONSULTAN PAJAK - Sri Ayem; Yhoga Heru Pratama; Selvianus Katoda (LPPM STIE YKPN Yogyakarta, 2024)
This study aims to examine whether career motivation, self-actualization motivation, creativity, taste and intention influence the interests of accounting students to become tax consultants. This research method uses primary quantitative and descriptive methods by using primary data obtained through the distribution of online questionnaires with accounting student respondents on several campuses in special regions of Yogyakarta. This research research questionnaire consisted of 71 questions and was filled by 71 respondents. The sampling technique uses purposive sampling. Data were analyzed using multiple linear regression analysis. The results of this study indicate that career motivation, self-actualization motivation, taste and intention have a positive influence on the interests of accounting students to become tax consultants while copyright has a negative influence on the interests of accounting students to become tax consultants.